EXTH-29. DUAL TGFB AND PD1 BLOCKADE PROMOTES GERMINAL-CENTER B-CELL IMMUNE RESPONSES AGAINST GLIOBLASTOMA. (12th November 2021) - Dapash, Mark; Hou, David; Castro, Brandyn; Rashidi, Aida; Zhang, Peng; Stupp, Roger; Miska, Jason; Lesniak, Maciej; Chang, Catalina
Abstract: In contrast to other malignancies such as melanoma and sarcoma, Glioblastoma (GBM) remains difficult to treat with immunotherapies. Recent studies have shown that positive immunotherapeutic responses are mediated by the accumulation of germinal-center-like B cells which are predictive of survival in patients treated with neoadjuvant PD1 blockade. In contrast, GBM-associated B-cells are scarce and the establishment of germinal-center like cells have not been observed. This study seeks to identify how B-cells are driven towards their immunosuppressive phenotypes in GBM and how this prevents immunotherapeutic efficacy. Utilizing single-cell RNA sequencing (scRNA-seq) in a CT2A murine glioma model, TGFb receptors 1 and 3 were identified as the most highly expressed inhibitory receptors on GBM-associated B cells. Furthermore, using scRNA-seq, TGFb1 was identified as the most highly expressed immunosuppressive cytokine in the TME, which was produced principally by tumor-associated myeloid cells (TAMCs). Inhibiting the myeloid compartment using intracranial anti-Gr1 antibody in combination with PD1 blockade resulted in B-cells exhibiting greater proliferation and differentiation into memory B-cells in addition to germinal-center-like B-cells. Further demonstrating B-cell functional reprogramming, autologous T cells isolated from spleens exhibited greater proliferation and robust anti-tumor cytotoxicity when cocultured with tumor-associated B-cells from the dual treatment group. Finally, inhibiting a5b8 integrin, a key complex in releasing active TGFb, increased tumor-infiltrating proliferating B-cells and conferred a long-term survival benefit in the CT2A murine model. Our results demonstrate that the immunosuppressive TME of GBM is influenced by the vital interplay between B-cells and the TME through TGFb signaling. This study highlights the potential therapeutic benefits of targeting the TGFb signaling pathway in conjunction with the current standard of care for GBM.